2015
DOI: 10.1039/c4cc08439j
|View full text |Cite
|
Sign up to set email alerts
|

A long-life Na–air battery based on a soluble NaI catalyst

Abstract: A Na-air battery with NaI dissolved in a typical organic electrolyte could run up to 150 cycles with a capacity limit of 1000 mA h g(-1). The low charge voltage plateau of 3.2 V vs. Na(+)/Na in a Na-air battery should mainly be attributed to the oxidation reaction of active iodine anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 15 publications
1
30
0
1
Order By: Relevance
“…Yin et al also reported the presence of this peak before charging their NaI-containing sodium-oxygen battery [21]. Based on this reaction it can be deduced that H 2 O and I 3 -would be chemically formed.…”
Section: Resultsmentioning
confidence: 93%
“…Yin et al also reported the presence of this peak before charging their NaI-containing sodium-oxygen battery [21]. Based on this reaction it can be deduced that H 2 O and I 3 -would be chemically formed.…”
Section: Resultsmentioning
confidence: 93%
“…The latter involves the electrochemical oxidation of Fe(C 5 H 5 ) 2 into Fe(C 5 H 5 ) 2 + (electrochemistry), according to UV absorption spectra of the electrolytes containing Fe(C 5 H 5 ) 2 after the battery directly charged to 3.5 V, then the oxidized product (Fe(C 5 H 5 ) 2 + ) will spontaneously react with Na 2 O 2 formed in the discharge process to re-produce Fe(C 5 H 5 ) 2 and release O 2 at the air electrode side. As previously reported for air batteries in pure oxygen environment, the catalyst exhibits either the electrocatalytic properties 7,22,23 or electrochemistry 14 .While, the liquid redox catalyst of Fe(C 5 H 5 ) 2 , homogeneous dissolving in the electrolyte, possesses the feature of dual catalytic behaviors as electrocatalyst and electrochemistry. In addition, the lower charge potential at about 3.1-3.2 V can avoid the decomposition of electrolyte and thus prolong cycle life of SABs.…”
Section: Resultsmentioning
confidence: 78%
“…The schematic diagram of a typical Na–air battery is shown in Figure A. However, sodium peroxide and peroxide dehydrate are also reported in literature . Interestingly, the theoretical calculation on the surface energies of various sodium oxide crystals with energy of bulk compounds suggests that bulk sodium peroxide is a more stable phase under standard operating conditions and sodium superoxide is more stable at the nanoscale under elevated oxygen partial pressures .…”
Section: Sodium–air Batteriesmentioning
confidence: 73%
“…Meanwhile, soluble catalysts are also very important in Li–/Na–air battery systems. So far, ethyl viologen redox couple, halide anions, aromatic compounds, quiones/quinoids, and transition metal complexes have been successfully applied in metal–air systems, where the battery shows much improved battery cyclic life and smaller overpotential …”
Section: Introductionmentioning
confidence: 99%